A hidrostática ensinada através de experimentações em sala de aula - (:unkn) unknown (Universidade Federal de Goiás, 2020)
There is a growing daily lack of interest among high school students in the exact sci-ences subjects. This attitude stems, among other factors, from the difficulty most students have in dealing with fundamental mathematical concepts (proportion, directly and inversely propor tional quantities, functions etc.), elementary arithmetic calculations (the four basic operations), and reading and interpretation of texts. Thus, the purpose of this proposal is to verify the real impact that the use of classroom experimentation has on the significant learning of high school students. We start from the conception that experimentation is a way of favoring the establishment of a link between the world of objects, the world of concepts, laws and theories and that of symbolic languages. Given this, we propose strategies for teaching hydrostatic content, using experimentation as a way to stimulate students' interest in knowing and understanding important physics content and to participate in classroom discussions on the subject.
Hydrostatics learned through classroom experiments
Keywords: Ensino de Física; Hidrostática; Ludicidade; Experimentação; Physics teaching; Hydrostatic; Playfulness; Experimentation; CIENCIAS EXATAS E DA TERRA::FISICA